Vegetation analysis of two insectivorous plants in Padang Pinang Anyang, Belitung Island - SYAMSUL HIDAYAT; JAJAT HIDAYAT; HAMZAH E. SUHANDI; TATANG TATANG; AJIDIN AJIDIN (Society for Indonesian Biodiversity, 2003)
Nepenthes gracilis and Drocera burmannii are rare species, found at Padang Pinang Anyang, Belitung island . These unique plants are also known as insectivorous species. Field observation was conducted on June, 2002. The number ofpopulation of N. gracilis and D.burmanii as well as identification of plants associated with have been carried out. Six transects, 50 x 5 m2 in each transect were established, of which one transect consists of 10 small 5 x 5 m2 plots. All plant species in plots were identified. The degree association is computed by contingency table 2x2 while distribution type is considered by variant. As the result, 19 species have recorded including grass species (44%), shrub (28%), tree (19%), and insectivorous plants (9%). The important value index (IVI) of N. gracilis 1.98, and D. burmannii 0.99.Â© 2003 Jurusan Biologi FMIPA UNS SurakartaKey words: insectivorous plants, population, association, distribution.